Political Legacies: Understanding Their Significance to Contemporary Political Debates. Issue 3 (10th April 2019) - Fong, Christian; Malhotra, Neil; Margalit, Yotam
ABSTRACT: Politicians bequeath an important legacy after they leave office: the public's memories of their time in office. Indeed, the media often discuss legacy concerns as a key motivation of politicians. Yet, there has been little empirical analysis of how politicians' legacies are interpreted and used by the mass public. Analyzing millions of comments from online discussion forums, we show that citizens frequently mobilize memories of past politicians in their discussions of current events. A randomized survey experiment rationalizes such invocations of past politicians: they bolster the persuasiveness of contemporary arguments—particularly bad ones—but only when made in the context of a policy domain specifically associated with a past politician. Our findings suggest that politicians have a strong interest in cultivating a positive, broad, and enduring legacy because memories of them influence policy debates long after they leave office.